EFFECTS OF SELECTED SOIL PROPERTIES ON GROWTH OF HALOXYLON SP. IN SEGZI PLAIN (IRAN) - A. Mojiri; A. Jalalian; N. Honarjoo (Journal of Animal and Plant Sciences, 2011)
This study evaluated the effects of soil properties on growth of Haloxylon sp. in Segzi plain in the Eastern of Isfahan province (center of Iran). One way to prevent the spread of blowing sand in a desert area is the biological fixation such as Haloxylon sp. For this research, a total of 12 profiles were studied. Depth of hardpan from the soil surface was determined. Then the soil samplings of 0-30, 30-60, 60-90, 90-120 cm depth were done. Plant physiological parameters, including plant height and top were measured. In the study area, Haloxylon sp. plants were all of similar age. Soil physical and chemical characteristics such as soil texture, total nitrogen (TN), pH, electrical conductivity (EC), chloride ions (Cl) and sodium absorption ratio (SAR) were measured. For analysis of the SPSS software was used to compare the statistics and averages. These results showed that the EC, SAR, Cl, pH and the percentage of clay had negative effects on plant physiologic parameters. The percentage of sand and depth of hardpan from the soil surface had positive effects on plant parameters.
Keywords: Alkalinity; Chloride ions; Haloxylon sp.; Pearson correlation; Salinity; Soil